Assessing Evidence-Based Practice in Operating Room Nursing Students: A Cross-Sectional Study in the Southwest of Iran - Jamshid Eslami; Amir Arsalan Saeedi; Majid Najafi Kalyani (The Scientific World Journal)
Evidence-based practice (EBP) is a clinical decision-making process that is grounded in the utilization of the most reliable and up-to-date evidence. It involves utilizing resources and evidence to enhance patient management. The application of evidence-based decisions in patient care and education is of utmost importance in the performance of health sciences students. However, the emphasis on this concept among operating room nursing students has been lacking. Hence, the objective of this research is to assess the implementation of evidence-based practice among operating room nursing students studying in the operating room department at the Shiraz University of Medical Sciences in Iran. The study follows a descriptive, cross-sectional design, with a sample of 148 operating room nursing students selected through census sampling based on the student list. After obtaining informed consent, participants completed a demographic information form and the Rubin–Parrish evidence-based practice questionnaire. The data that were gathered underwent analysis through the utilization of SPSS version 22 software, employing descriptive statistics, T-tests, and Pearson correlation coefficient tests. The results revealed that the overall average score of evidence-based practice among the students exceeded the standard scores (172.66 ± 14.74). There was a significant association between the evidence-based practice score and prior familiarity with evidence-based practice, interest in the field of study, research experience, intention to participate in the Master’s exam, and the participants’ grade point average (GPA) (p<0.05). These findings indicate that operating room nursing students displayed an average level of evidence-based practice, emphasizing the need for effective plans and strategies to improve their performance. Addressing the identified factors from this study becomes crucial in this regard.